Determinants of working capital of 60 industrial manufacturing firms listed on Hnx & hose - Ta, Thi Hong Van (2020)
Corporate finance is about decision-making on three different fields: capital structure, capital budgeting and working capital management (Ross, Westerfield and Jaffe 2010). Predominantly, the focus within the corporate finance literature has been on studying long-term financial decisions such as investments in fixed assets, capital structure, dividend policy and corporate valuation.